Desafios Políticos da União Européia - Volpi, Almir (2006)
In the last 20 years, Europe has been investigating solutions to its institutional stability in the geopolitical scenario, which makes constant change in the European environment. The quest for solutions based on Treaties (Maastricht, Amsterdam and Nice) has established a historical platform that consequently has generated huge debates over European integration. After the last widening and the launching of the European Constitution, still under controversial discussions about ratification, Europe continues looking for a direction: how will Europe with constant widening work? Which political model will be adopted Confederal, Federal or a mix of both or other one that will be developed by European politicians? These questions are still with no answers and result in an institutional instability. The questions about what to do and how to do to aggregate the political environment Europe has been going through for decades, seem to be far to be established. Thus, the goal of this study is to identify whether or not the modifications resulted from the mentioned Treaties have established some base to the political option to be adopted by the block during its construction process. The hypothesis to be considered analysis if European Union steps forward a political model not yet defined that presents itself as an unknown cut. It is analyzed the Union political issues pos-Maastricht and their changes instituted by Treaty of Nice, by verifying the documents of the Intergovernmental Conferences and Treaties which had established the European Union, and also the European Constitution. After it is possible to identify the evolution path of the political union whose unification, at this moment, demonstrates to be a real possibility. The presented questions are diverse to a reference of the real political construction that allows the establishment of a huge union with continuous candidates to the widening and also maintains discussion and cohesion capacities, needed to reach the fundamental goals furthermore guarantees the consolidation of the integration process development